294 CD8 PET imaging of tumor infiltrating T cells in advanced solid tumors: a phase I first-in-human study of 89Zr-IAB22M2C, a radiolabeled anti-CD8 minibody. (10th December 2020) - Farwell, Michael; Gamache, Raymond; Pandit-Taskar, Neeta; Postow, Mike; Gordon, Michael; Wilson, Ian; Mascioni, Alessandro; Wu, Anna; Le, William; Weiss, Avital; Korn, Ronald
Abstract : Background: Tumor infiltration by CD8 T cells is associated with favorable outcomes to immunotherapy (IOT). However, biopsies to assess T cell infiltration are invasive and prone to sampling error. CD8 PET imaging could provide an effective non-invasive method of visualizing T cell trafficking and tumor infiltration and predicting early response to IOT. Methods: A phase 1 first-in-human PET imaging study using an anti-CD8 radiolabeled Minibody, 89Zr-IAB22M2C (CD8-tracer), to detect whole body and tumor CD8 distribution in patients with metastatic solid tumors was completed. Patients received 3 mCi 89Zr-IAB22M2C followed by serial PET scans over a 5–7-day period. A two-stage design included protein dose escalation phase 1 (n=6, 0.2 mg to 10 mg API) to establish safety and optimal scanning parameters and a dose expansion phase focusing on two API doses (0.5 mg (n=4) or 1.5 mg (n=5) API). All patients were monitored for drug-related adverse events with blood chemistry, hematology, cytokine assay and anti-drug antibodies (ADA). Biodistribution, radiodosimetry and SUV PET uptake was performed in all patients. Results: 15 subjects (31–82 years, M/F = 9/6) with metastatic melanoma (n=8), NSCLC (n=6), and HCC (n=1) were enrolled. Treatment histories included naïve (n=2), discontinued prior IOT (n=3), active IOT (n=10). No drug-related AEs nor abnormal laboratory tests were noted except for a transient increase in ADA in 1 subject. The CD8-tracer accumulated in tumors and CD8 rich tissues (e.g. spleen, marrow, nodes) with maximum uptake at 24–48 hours post injection along with low background activity in non-T cell rich tissues (e.g. muscle, heart). More favorable dosimetry was seen at 1.5 mg versus 0.5 mg API (effective dose=0.64 mSv/MBq versus 0.67 mSv/MBq, respectively). Comparison of 1.5 mg and 0.5 mg API in expansion cohorts demonstrated similar uptake in nodes but with reduced uptake in marrow and spleen at the higher API. Tracer-uptake in tumors was noted in 10/15 (67%) subjects, favoring slightly higher tumor uptake in the 1.5 mg cohort. One patient with advanced melanoma on IOT had increased CD8-tracer uptake in several metastases on an early post treatment scan, which correlated with response (figure 1 ). Conclusions: 89Zr-IAB22M2C targets CD8+ rich tissues and visualizes whole-body biodistribution of CD8+ cells in tumors and reference tissues and may predict early response to IOT. A 1.5 mg protein dose provides similar distribution to 0.5 mg dose, with more favorable dosimetry and is used in the ongoing Phase 2 study. Acknowledgements: None Trial Registration: ClinicalTrials. gov Identifier: NCT03107663 Ethics Approval: The study was approved by Institutional Review Boards of MSKCC (IRB #16-1109), Honor Health (West IRB #1179278) and University of Pennsylvania (IRB # 828992). Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal. Reference: Michael S. Gordon, MD et al, November 2018, Imaging of tumor infiltrating T cells with an anti-CD8 minibody 89Zr-IAB22M2C in advanced solid tumors: a phase I first-in-human study, presented at 33th Annual SITC meeting (session O48).